A Survey on The Methods of Spatial Statistics - Sayed, Hawri Hashm (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: In this thesis the kriging approach is presented for interpolating spatial data points. The mathematical model of the kriging method is mentioned first. Then a small example is provided about the steps of this approach. ArcGIS software package is an important tool for creating maps and also for performing geostatistics about large data points. A kriging example is also tried by this package and the predicted data points are listed. Keywords: Geostatistics, spatial data, kriging, Arcgis. ………………………………………………………………………………………………………………………… ÖZ: Bu çalışmada, harita bilgileri (kordinatlar) üzerinde enterpolasyon uygulamalarında kullanılan kriging metodu bahsedilmektedir. Bu metodun matematiksel modeli yanında, seçilen küçük bir very örneği kullanılarak hesaplamalarla yaklaşık kestirme değerleri hesaplanmıştır. Bu analiz için geniş verilerin kullanılmasında en önemli yazılımlardan olan Arcgis paketi de kullanılarak seçilen verilerin analizi ve kestirim sonuçları eğrilerle birlikte sunulmuştur.
Master of Science in Applied Mathematics and Computer Science. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2014. Supervisor: Assist. Prof. Dr. Mehmet Ali Tut.
Keywords: Mathematics; Applied Mathematics and Computer Science; Spatial analysis (Statistics); Mathematical statistics - Data processing; Geostatistics, Spatial Data, Kriging, Arcgis